Estratégias de compreensão leitora: uma proposta de atividades didáticas para o trabalho com o gênero videoanimação - Silva, Aline Iracy Rodrigues (2021)
This research was motivated by provocations concerning the challenges inherent to teaching and learning the practice of reading, based on the question: How can reading strategies be explored in video animations? Thus, we defined the general objective of this research: Present work proposals with the video animation genre by articulating between theory and practice. Justified by the contributions that this work can add to the training of teachers, the proposal in question aims to stimulate the production of knowledge on the strategies to be used for reading video animations. We chose two types of research: a) bibliographical research and b) the production of a didactic proposal, which includes working with the video animation genre. This research is qualitative, exploratory in nature, based on the theoretical contributions of Solé (1998), aimed at discussing reading strategies. The research concerning the video animation genre discussion is based on Ferreira and Villarta-Neder (2020) and Ferreira, Dias, and Villarta-Neder (2019). The research also presents an applied approach, contemplating a proposal for a pedagogical notebook as an educational product. The research made it possible to compile theorists who address reading and articulate strategies for reading multisemiotic texts, especially for the video animation genre. Thus, theories on reading strategies can clarify the development of educational activities related to reading video animations, expanding the potential of this genre for the formation of critical and proficient readers as a function of the social themes explored and the diversity of semiosis that constitute this type of production.